Photopleochroism of surface-barrier structures based on semiinsulating cadmium telluride - Ilchuk, G.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
The method of mass-transfer reaction with compounds NH₄ (Cl, Br, J) as a transроrting agent is developed, and single crystals of semiinsulating CdTe are grown. Interaction of plane-polarized radiation with In-p-CdTe barrier fabricated on these single crystals is investigated. It is shown that at incidence of plane-polarized radiation at incidence angle Q > 0° upon a surface of barrier the induced photopleochroism appears and it is proportional to the angle squared. The conclusions about the high quality both of the single crystals obtained by chemical transport reactions and of the interface of the structures as well as about the possibilities for using such structures as polarimetric analyzers of radiation are made.